Progress on HIV and other sexually transmitted infections elimination among youth and adults across BRICS-plus countries: Results from the Global Burden of Disease Study 2021 - Rizhen Wang; Yinuo Sun; Huan Wang; Xiaoran Yu; JiYan Ma; Zuokun Liu; Jing Li; Zhiyong Zou; Yangmu Huang (Journal of Infection and Public Health)
Background: Global strategies aim to eradicate HIV and other sexually transmitted infections (STIs) by 2030. We aim to assess HIV and other STIs morbidity trends from 1992 to 2021 across BRICS-plus (Brazil, Russia, India, China, South Africa, Egypt, Ethiopia, Iran, Saudi Arabia, and the United Arab Emirates), which accounts for nearly half of the world population. Methods: HIV and other STIs morbidity estimates were derived from the Global Burden of Disease Study 2021. We derived percentage changes to evaluate the progress towards HIV 2020 milestones and annualised rate of change to determine the progress needed to achieve 2030 targets. We used age-period-cohort (APC) model to estimate period (cohort) relative risks for both disease areas. Results: Around 46 % of global incident cases attributed to HIV and other STIs were found in BRICS-plus countries, exceeding the combined totals of North American countries. The HIV new cases in BRICS-plus declined by 8.2 % between 2010 and 2020. No countries within BRICS-plus achieved a target of a 75 % decrease in HIV new cases in 2020 or 2021, but India (-41.7 %), Ethiopia (-34.4 %), China (-29.7 %), and South Africa (-11.7 %) showed reductions. Individuals aged 15–24 years (-32·9 %) had a decline for HIV new cases, while individuals aged ≥ 25 years plateaued. There were evident period risks of morbidity for HIV in Russia and Iran since 2012 and for syphilis and gonorrhea in Brazil since 2012. Younger generations had a higher risk of contracting HIV in Brazil, China, Egypt, Iran, and Russia, and other STIs in Brazil, India, Iran, and South Africa, particularly genital herpes. Conclusion: BRICS-plus was still far from reaching the global 2030 targets for both disease areas. Adults aged ≥ 25 years have little progress in HIV new cases, and youth and adults in other STIs.